Quality improvement of unfiltered holography by optimizing high diffraction orders with fill factor - Zhou, Jie; Wang, Jiabao; Yu, Guangwei; Wu, Yang; Wang, Mohan; Wang, Jun (Optics letters, 2024)
Computer-generated holography (CGH) suffers from high diffraction orders (HDOs) due to the pixelated nature of spatial light modulators (SLMs), typically requiring bulky optical filtering systems. To address this issue, a novel unfiltered holography approach known as the high-order gradient descent (HOGD) algorithm was previously introduced to optimize HDOs without optical filtering, enabling compact holographic displays. However, this algorithm overlooks a crucial physical parameter of SLMs-the fill factor-leading to limited optical quality. Here, we introduce a fill factor-based HOGD (FF-HOGD) algorithm, specifically designed to improve the quality of unfiltered holography by incorporating the fill factor into the optimization process. The quality advantage of FF-HOGD is demonstrated through numerical simulations and optical experiments.